Istana Besar Tengku Long : wall carving decoration and motifs influences the spatial social interaction at Surung Area / Shamsidar Hj. Ahmad, Mohd. Zafrullah Hj. Mohd. Taib dan Mawar Hj. Masri - Ahmad, Shamsidar; Mohd. Taib, Mohd. Zafrullah; Masri, Mawar (2012)
Woodcarving is considered as an integral component to the vernacular Malay house in Peninsular Malaysia. This research aimed to promote deeper understanding of wall carving decoration and motifs found in the Malay traditional houses influences social interaction at “surung” area. A case study performed at “Istana Besar Tengku Long” in Kuala Terengganu, Terengganu. The research method included literature review, measured drawing, interviewed with local well-known woodcarvers incorporated with late Tengku Long generation. As a results, the application of carvings at surung” are contained a practices concerning teaching good direction and high-quality ways of life to the Malay society.